Do countries adopt a mimicry process to tackle the issue of climate change? An international comparative analysis of the carbon economy with specific reference to the EU, Australia, China and Indonesia - Ratnatunga, Shehan Tissa Mahendra (2012)
Climate change is a serious and urgent issue caused by the increasing greenhouse gases emitted into the atmosphere from human activities. The changes in the physical world resulting from rising global temperatures are likely, if anything, to be more harmful than earlier believed. The Kyoto Protocol was the first international treaty signed in 1998 which attempted to address the adverse impacts of climate change by committing ratifying countries to attaining agreed targets on emissions reduction. As there is no mandatory prescription for a decarbonising policy framework, a wide variety of carbon-reducing policy instruments can be observed in different countries each with its own different compliance requirements.